Analisis Kelengkapan dalam Merumuskan Tujuan Pembelajaran pada Mahasiswa PGMI Semester V - Pitasari, Mely; Dwi Febriyanti, Beby (Universitas Muhammadiyah Sorong, 2023)
This study aims to determine the formulation of learning objectives developed by PGMI students in semester V in accordance with the ABCD learning objectives model, namely audience, behavior, condition, degree. The research method used is a qualitative descriptive research method, the author will describe and explain how students make learning objectives. The results of this research were obtained that there are still many students who have not mastered how to make learning objectives in accordance with the ABCD model, Most of the difficulties in formulating the Condition component, some students make learning objectives incomplete